Applications of chitosan nanoparticles to enhance absorption and bioavailability of tea polyphenols: A review. (August 2017) - Liang, Jin; Yan, Hua; Puligundla, Pradeep; Gao, Xueling; Zhou, Yibin; Wan, Xiaochun
Abstract: Tea polyphenols find a wide range of applications in food, medical and pharmaceutical fields owing to their multi-health benefits including antioxidant and antibacterial activities, cancer prevention, anti-radiation and immune enhancement. However, the low absorption rate of tea polyphenols impedes their bioactivity in vivo. The low absorption and bioavailability have been attributed to their poor stability, passive diffusion, and active efflux in the gastrointestinal (GI) tract. Nanoparticle delivery system based on chitosan (CS), a natural biomaterial, has been widely applied in pharmaceutical field to enhance absorption of bioactive compounds. A few studies reported the enhanced absorption and bioavailability of tea polyphenols by the application of chitosan nanoparticles. This review describes the fabrication methods and potential benefits of chitosan nanoparticles as delivery systems for tea polyphenols for their enhanced absorption in the GI tract. In addition, challenges and future trends of chitosan nanoparticles as a carrier for oral delivery of tea polyphenols are also discussed. Graphical abstract: Chitosan nanoparticles enhance the intestinal absorption of tea polyphenols. Highlights: The low absorption rate of tea polyphenols impedes their bioactivity in vivo. Nanoparticle delivery system based on chitosan can enhance absorption of bioactive compounds. The fabrication methods and potential benefits of chitosan nanoparticles in tea polyphenols delivery were described. The challenges and future trends of chitosan nanoparticles as a carrier for oral delivery of tea polyphenols are discussed.